Scholarly Communication Librarian Tantangan Tupoksi Pustakawan di Era 4.0 - Dini Suhardini; Lisna Nurhalisma; Isma Anggini Saktiani; Luqman Fauzi (Perpustakaan Nasional, 2022)
Scholarly communication librarian (SCL) is the involvement of librarians to facilitate researchers to know the development of research conducted by other researchers. Scholarly communication is not a new thing in the library world, because scientific publishing has existed since the research was conducted. The purpose of this study was to find out SCL as a challenge for librarian duties in era 4.0 which includes three main tasks of librarians in legislation, library management, library services, and librarianship system development. The population in this study were members of the FPPTI Jawa Barat and a sample of 70 people based on the Slovin formula with an error rate of 10%. The study used a descriptive method with a quantitative approach and data collection techniques using a closed Likert scale questionnaire. Based on the results of the data analysis, it shows that the FPPTI Jawa Barat librarian gave a positive response with a very good category in the SCL. FPPTI Jawa Barat librarians in carrying out their role as SCL have been able to adapt quickly and make important contributions in conducting research. The results of the study illustrate that the FPPTI Jawa Barat librarian has carried out library management well, especially in planning and evaluation, providing various sources of information that are easily accessible to users, quick reference, and conducting scientific writing guidance, and being a facilitator. The involvement of librarians in conducting research shows that FPPTI Jawa Barat librarians are actively involved in research to improve library performance in realizing service excellence.